1988
DOI: 10.1037/0033-2909.104.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Excuses: Their effective role in the negotiation of reality.

Abstract: Call for Nominations for Editor of Behavioral NeuroscienceThe Publications and Communications Board has opened nominations for the editorship of Behavioral Neuroscience for the years 1990-1995. Richard F. Thompson is the incumbent editor. Candidates must be members of APA and should be available to start receiving manuscripts in early 1989 to prepare for issues published in 1990. Please note that the P&C Board encourages more participation by women and ethnic minority men and women in the publication process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
4
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(253 citation statements)
references
References 94 publications
12
228
4
8
Order By: Relevance
“…The items that formed a reliable measure from the rating scale all concerned pejorative self-blame statements ("I was not smart enough to stop it from happening") whereas the open-ended question elicited responses that some have labeled self-excusing attributions ("The abuse happened because I was too young to stop it from happening"). Self-excusing attributions place the locus of cause on the self but without the same negative valence as pejorative self-blame statements (Snyder & Higgins, 1988). To some extent such attributions serve to exonerate the self from intensely negative blame (McGee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The items that formed a reliable measure from the rating scale all concerned pejorative self-blame statements ("I was not smart enough to stop it from happening") whereas the open-ended question elicited responses that some have labeled self-excusing attributions ("The abuse happened because I was too young to stop it from happening"). Self-excusing attributions place the locus of cause on the self but without the same negative valence as pejorative self-blame statements (Snyder & Higgins, 1988). To some extent such attributions serve to exonerate the self from intensely negative blame (McGee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, train delays have important reputational and financial costs (Brown & Beltramini, 1989;Folkes et al, 1987;Wang & Huff, 2007). One way to reduce these costs is to provide an excuse that points out the external forces contributing to the delay (Kim et al, 2009;Shaw et al, 2003;Snyder & Higgins, 1988). An efficient way to communicate such excuses to the passengers is to incorporate them in the message that announces the delay.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that the influence of inadequate service provision was reduced when consumers did not expect the event to reoccur (Folkes et al, 1987;Wang & Huff, 2007), evaluated the inconvenience as small (Brown & Beltramini, 1989), or felt that the supplier had no control over the situation (Brown & Beltramini, 1989;Folkes et al, 1987). As a result, an interesting approach to repair trust is to provide an excuse that lists the external factors contributing to the transgression (Kim, Dirks, & Cooper, 2009;Shaw, Wild, & Colquitt, 2003;Snyder & Higgins, 1988). Interestingly, train delays are often the result of factors beyond the control of the railway company.…”
Section: Introductionmentioning
confidence: 99%
“…A teoria da atribuição de causalidade, por meio de seus variados modelos, é a abordagem que substancia a maior parte dos trabalhos sobre desculpas em psicologia social (Basgall & Snyder 1988;Snyder & Higgins, 1988;Weiner, Folkes, Amirkhan, & Verette, 1987). As explicações que os indivíduos dão, tanto para os seus próprios comportamentos quanto para os de outras pessoas, constituem o objeto de análise destas teorias (Heider, 1944(Heider, , 1958, focando o tipo de atribuição como uma variável dependente.…”
Section: Atribuição De Causalidade E Desculpasunclassified
“…Também se deve reconhecer que o tipo de mecanismo associado ao pedido de desculpas, entre outras lógicas que afastam a responsabilidade das pessoas das suas falhas, pode ser algo benéfico e até saudável (Snyder & Higgins, 1988). As desculpas preservam o autoconceito dos indivíduos e aliviam efeitos negativos relacionados a seus resultados culposos (Taylor & Brown, 1988).…”
unclassified